2014
DOI: 10.1016/j.fertnstert.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of the impact of hot flashes on sleep in perimenopausal women

Abstract: Objective To quantify the impact of objectively-recorded hot flashes on objective sleep in perimenopausal women. Design Cross-sectional study. Participants underwent 1–5 laboratory-based polysomnographic recordings for a total of 63 nights, including sternal skin conductance measures, from which 222 hot flashes were identified according to established criteria. Data were analyzed with hierarchical mixed-effect models and Spearman correlations. Setting Sleep laboratory. Patients 34 perimenopausal women (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 44 publications
(60 reference statements)
5
64
0
2
Order By: Relevance
“…We evaluated sleep spindle characteristics in addition to EEG activity and could show clear increases in spindle density and spindle duration in the luteal phase. We also measured hot flashes because hot flashes are known to disturb sleep (40,41). In this sample of early-transition women, few women had hot flashes; these events are likely to disrupt sleep more in late transition and early postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated sleep spindle characteristics in addition to EEG activity and could show clear increases in spindle density and spindle duration in the luteal phase. We also measured hot flashes because hot flashes are known to disturb sleep (40,41). In this sample of early-transition women, few women had hot flashes; these events are likely to disrupt sleep more in late transition and early postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…13 Poor sleep is reported especially in the presence of vasomotor symptoms. 2,4,14,15 Nevertheless, even today the researchers are not unanimous about the primary cause of menopausal sleep disturbance. In addition to fluctuations and decrease in reproductive hormone concentrations, aging itself, 16 depressive symptoms, 17,18 sleep-disordered breathing, primary sleep disorders, other systemic diseases and/ or their medications as well as psychosocial or behavioral factors may contribute to sleep impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in midlife women have shown that nocturnal hot flashes were most likely to occur during stage N2 sleep and are commonly linked with an awakening. [1][2][3] The link between nocturnal hot flashes and awakenings has raised the question of whether hot flashes directly induce awakenings. Evidence supporting this explanation includes data from peri-and postmenopausal women showing that 54% to 69% of objectively measured nighttime hot flashes are associated with an awakening.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting this explanation includes data from peri-and postmenopausal women showing that 54% to 69% of objectively measured nighttime hot flashes are associated with an awakening. [1][2][3] Among those hot flashes occurring proximate to an awakening, the specific temporal sequence between the onset of the awakening and the flash beginning varies, with studies showing that objectively measured nighttime hot flashes precede or begin simultaneously with the awakening 54% to 90% of time. [1][2][3] The observation that a hot flash can begin after the onset of the awakening in some hot flash/wake episode pairs, particularly during the second half of the night, 3 the possibility that hot flashes do not uniformly induce awakenings, 2 even when they are temporally linked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation